2008
DOI: 10.1039/b714924g
|View full text |Cite
|
Sign up to set email alerts
|

Solid-phase synthesis of graphitic carbon nanostructures from iron and cobalt gluconates and their utilization as electrocatalyst supports

Abstract: We present a novel and facile synthesis methodology for obtaining graphitic carbon structures from Fe(II) and Co(II) gluconates. The formation of graphitic carbon can be carried out in only one step by means of heat treatment of these organic salts at a temperature of 900 1C or 1000 1C under inert atmosphere. This process consists of the following steps: (a) pyrolysis of the organic gluconate and its transformation to amorphous carbon, (b)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 64 publications
4
42
0
Order By: Relevance
“…those reported for electrocatalysts supported on other forms of graphitic carbon, such as mesocarbon microbeads [22], onion-like fullerenes [23], single-wall carbon nanotubes [24] or multiwalled carbon nanotubes [25]. We recently achieved similar ESA values for catalysts made up of Pt nanoparticles deposited on GCNs obtained from pine sawdust [10] and Fe(II) and Co(II) gluconates [11]. V for Pt/Vulcan is attributed to methanol electrooxidation.…”
Section: Electrocatalytic Activity Of the Pt/gcnssupporting
confidence: 62%
See 1 more Smart Citation
“…those reported for electrocatalysts supported on other forms of graphitic carbon, such as mesocarbon microbeads [22], onion-like fullerenes [23], single-wall carbon nanotubes [24] or multiwalled carbon nanotubes [25]. We recently achieved similar ESA values for catalysts made up of Pt nanoparticles deposited on GCNs obtained from pine sawdust [10] and Fe(II) and Co(II) gluconates [11]. V for Pt/Vulcan is attributed to methanol electrooxidation.…”
Section: Electrocatalytic Activity Of the Pt/gcnssupporting
confidence: 62%
“…Likewise, we analyzed the use of commercially available iron or cobalt organic salts (i. e. Fe (II) gluconate and Co (II) gluconate) as precursors. These have the advantage of providing both the metal catalyst for the graphitization and the carbon source [11]. However, it is important to point out that the use of sawdust or gluconates as carbon precursor to fabricate GCNs has some limitations.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the fact that the GCNC do not possess any framework-confined porosity [15], so their entire surface area is external and therefore of easy access. We recently obtained similar results for catalysts made up of Pt nanoparticles deposited on carbon nanostructures obtained from pine sawdust [11] and Fe (II) and Co (II) gluconates [12].…”
Section: Electrochemical Characterization Of Pt Nanoparticles Supportsupporting
confidence: 58%
“…Likewise, we have analyzed the use of commercially available iron or cobalt organic salts (i. e. Fe (II) gluconate and Co (II) gluconate) as precursors [12]. A large number of research groups have demonstrated that the hydrothermal carbonization of saccharides constitutes a facile way to prepare carbonaceous microspheres with a high density of oxygen functional groups, which are useful in numerous applications and also as precursor for the synthesis of nanostructured inorganic materials [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…During this process, polymers first decompose to amorphous carbon (AC), after which AC, as the solid carbon source, dissolves in and precipitates out of the catalyst [16][17][18][19][20][21]. The dissolution and precipitation of AC is affected by the thermal treatment temperatures.…”
Section: Introductionmentioning
confidence: 99%